Note of clarification of data in the paper entitled “Interferon gamma +874 T/A polymorphism increases the risk of cervical cancer: evidence from a meta-analysis” - Haijun Yang; Min Yang; Yan Wang; Xing Huang (Tumor Biology)
We read with great interest the paper entitled “Interferon gamma +874 T/A polymorphism increases the risk of cervical cancer: evidence from a meta-analysis” published online by Sun et al. Their results suggest that interferon gamma ( IFNG ) gene +874 T/A polymorphism might contribute to women’s susceptibility to cervical cancer. They also found that IFNG +874 T/A polymorphism is associated with increased cervical cancer risk in Asian female population. The result is encouraging. Nevertheless, several key issues are worth noticing. We re-evaluate the association between IFNG +874 T/A polymorphism and cervical cancer risk by performing an updated meta-analysis based on 2777 cases and 2542 controls of 11 studies. We found that IFNG +874 T/A polymorphism was not significantly associated with cervical cancer risk in overall population. We also observed that the polymorphism was associated with enhanced cervical cancer risk in Asian population and was relevant to increased squamous cell cervical cancer risk.